Development of geometry teaching materials based on RME in the context of the perahu baganduang tradition - Sri Marlini; Jesi Alexander Alim; Zetra Hainul Putra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This research aims to improve the mathematical communication skills of grade V elementary school students in mathematics subjects through geometry teaching materials based on Realistic Mathematics Education (RME) with the context of baganduang boats. This teaching material was developed on building flat and curved side spaces by emphasizing the relationship of mathematical concepts with daily life, so that abstract ideas are easier to understand. The research uses the Plomp model development method, which consists of three stages, namely preliminary research, prototyping phase, and assessment phase. In the initial stage, literature studies, curriculum analysis, and student needs are identified. Furthermore, the prototype of teaching materials that includes teacher books and student books is validated by three validators, then tested through one-to-one, small groups, and revisions according to field input. The final stage is in the form of a large group trial to assess the practicality and effectiveness of the teaching materials. The validation results show an average score of 0.89 (very valid). The practicality test obtained a score of 94.22% from students and 98.13% from teachers in small groups, as well as 95.8% from students and 99.16% from teachers in large groups (very practical). Effectiveness was shown through the N-Gain test of 0.8 (high category) with a percentage of 82.6% (effective). The score of mathematical communication ability increased from 45.6 (pretest) to 88.3 (posttest) with an average increase of 42.78 (sufficient category). Thus, RME-based geometry teaching materials in the context of baganduang boats have proven to be valid, practical, and effective in improving mathematical communication of elementary school students